ERROR ANALYSIS ON THE WRITING TEST BY THE SECOND YEAR STUDENTS OF MAN 3 MALANG - RAHMAWATI, TIARA HERMAN (Jurnal Ilmiah Mahasiswa FIB, 2014)
Keywords: Error analysis, error, types of error, writing test Language is the best means of communication to interact among people and to create a good relationship between them in society. Practicing language skills can be done by applying it in daily life in order to improve or master the language. Learning English is not easy; particularly for those where English is not the mother tongue. In Indonesia, English has been taught from Elementary school, Junior High School, Senior High school to the University level. Therefore, for Indonesians usually English is their first foreign language. In learning English, the students may make errors. It happens because between Bahasa Indonesia and English have different grammatical rules. The research problems of this study are (1) What are the types of English writing errors made by the second year students of MAN 3 Malang?; (2) What is the type of errors mostly done by the second year students of MAN 3 Malang?This study used descriptive qualitative approach and data analysis to answer the problems of the study. The data are the 16 papers from the second year students on final test papers. The final test papers were collected from one class (MABI) in MAN 3 Malang.The result of this study showed that the students did some types of errors when they wrote a writing test. Those are omission of auxiliary verb, omission of plural marker (-s/-es), omission of third person singular verb marker (-s/-es), omission of article (a/an/the), omission of verb, omission of subject and omission of noun. Then addition was divided into eight. They are addition of auxiliary verb be (is/am/are), addition of third person singular verb marker (-s/-es), addition of article (a/an/the), addition of plural marker (-s/-es), addition of conjunction, addition of preposition, addition of adjective, and addition of verb. Misformation consists six types, they are misformation of auxiliary verb be (is/am/are), misformation of verb, misformation of preposition, misformation of noun, misformation of reflexive pronoun, and misformation of adjective. The last is misordering. The total of number of errors is 84. The most frequent error that the writer found in the writing paragraph are omission (Om) with 23 errors (27%), addition (Ad) with 15 errors (18%), misformation (Mf) with 43 errors (51%), and misordering (Md) with 3 errors (4%).The writer suggests the next writers who want to conduct a similar study use the same theory with another object or use the same object with other theories or make their study more complete. The next writer can use another object, for example novels, short stories, articles or journals as the data.